2019
DOI: 10.14283/jfa.2019.31
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Frailty With Hospitalizations and Mortality Among Community Dwelling Older Adults With Diabetes

Abstract: Background: Diabetes (DM) is associated with an accelerated aging that promotes frailty, a state of vulnerability to stressors, characterized by multisystem decline that results in diminished intrinsic reserve and is associated with morbidity, mortality and utilization. Research suggests a bidirectional relationship between frailty and diabetes. Frailty is associated with mortality in patients with diabetes, but its prevalence and impact on hospitalizations are not well known. Objectives: Determine the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…In this study diabetics were at 1.36 (95% CI = 1.18, 1.56) and 1.56 (95% CI = 1.32, 1.85) fold increase in risk of frailty compared to non-diabetic population for prevalence and incidence respectively [ 10 ]. The research by Ferri-Guerra et al (2019) showed that in 763 DM patients (mean age 72.9 years) 50.5% were frail [ 52 ]. Other studies also confirmed that the prevalence of frailty in adults older than 65 years was three- to five-fold higher in patients with diabetes than that in the general population [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study diabetics were at 1.36 (95% CI = 1.18, 1.56) and 1.56 (95% CI = 1.32, 1.85) fold increase in risk of frailty compared to non-diabetic population for prevalence and incidence respectively [ 10 ]. The research by Ferri-Guerra et al (2019) showed that in 763 DM patients (mean age 72.9 years) 50.5% were frail [ 52 ]. Other studies also confirmed that the prevalence of frailty in adults older than 65 years was three- to five-fold higher in patients with diabetes than that in the general population [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from an overview of systematic reviews showed that 24/24 studies demonstrate an increased mortality risk for frail individuals while 7/7 showed a significant impact of pre-frailty in mortality [38]. The relation between frailty and mortality risk among other conditions in older adults was also studied, and it was found to increase the risk of death among diabetic patients [39], after hip fracture [40], after pelvic surgery [41], after mitral valve replacement [42], among others. Frailty is also associated with worse short term-term postoperative outcomes and mortality [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although guidelines agree that looser glycaemic control is more suitable for frail diabetic patients, the routine clinical practice still seems to miss the point. For example, in the study by Ferri-Guerra and colleagues (5), no significant difference was detected in the adherence to a tight glycaemic control between frail and non-frail patients (52.5% vs 57.9%, p=0.15). Frail diabetic participants were also more likely to be treated with agents exposing to a higher risk of hypoglycaemia.…”
mentioning
confidence: 87%
“…In conclusion, diabetic patients should be routinely assessed for frailty. As Ferri-Guerra and colleagues (5) showed in their work, frailty independently contributes to the burden of diabetes in terms of healthcare utilization and decreased survival. The identification of frailty should lead to careful evaluation and potentially to an adapted intervention (12,13).…”
mentioning
confidence: 93%
See 1 more Smart Citation